Single-Molecule Magnet Behavior in a Series of Defective Dicubane Zn 2 Dy 2 Tetranuclear Clusters with Diverse Anionic Coligands - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2025)
We present herein the structural and magnetic characterization of four defective dicubane complexes: [Zn2Dy2(L)4(NO3)2(H2O)2]<middle dot>2MeOH (1), [Zn2Dy2(L)4(mu-CH3COO)2(H2O)2]<middle dot>3H2O (2), [Zn2Dy2(L)4(mu-piv)2(MeOH)2]<middle dot>0.5CH3CN<middle dot>MeOH<middle dot>2H2O (3), and [Zn2Dy2(L)4(mu-nba)2(MeOH)2]<middle dot>3.5MeOH (4), synthesized using a new Schiff base ligand, 2-(5-tert-butyl-2-hydroxyphenylimino-methyl)-6-methoxy-4-methylphenol (H2L), along with various anionic coligands. The structure of H2L is particularly interesting due to the rare coexistence of both keto-amine and enol-imine tautomeric forms within a single crystal; however, upon complexation, the keto-amine form predominates. All four complexes exhibit remarkable single-molecule magnet (SMM) behavior, displaying significant magnetic relaxation in zero field, with the highest effective energy barrier (U eff) reaching 270 K for complex 4 and notable magnetic hysteresis temperatures. The SMM performance of complexes 1-3 is further enhanced under an applied magnetic field, with U eff values exceeding 200 K for all except complex 1, positioning them among the most promising Zn-Dy-based SMMs reported to date. These findings underscore the critical role of anionic coligands in modulating the dynamic magnetic relaxation properties by influencing the first coordination sphere around the DyIII ions. Ab initio calculations reveal that the shortest terminal phenoxide group predominantly governs the magnetic anisotropy, while the anionic coligands contribute to structural distortions and variations in transverse magnetic anisotropy, resulting in subtle differences in magnetic dynamics across the series. Overall, this study unveils the effects of coligands on the SMM performance in a series of defective-dicubane Zn2Dy2 complexes, enriching the field of Zn-Dy-based SMMs.